2013
DOI: 10.1016/j.jamda.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Postacute Care and Staffing in US Nursing Homes, 2001–2010

Abstract: Objective The objective of this study was to document the growth of postacute care and contemporaneous staffing trends in US nursing homes over the decade 2001 to 2010. Design We integrated data from all US nursing homes longitudinally to track annual changes in the levels of postacute care intensity, therapy staffing and direct-care staffing separately for freestanding and hospital-based facilities. Setting All Medicare/Medicaid-certified nursing homes from 2001 to 2010 based on the Online Survey Certific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…30 Over the past 15 years, staffing at nursing homes has stayed level in terms of nursing aide hours per resident per day. 28 The rate of obesity among nursing home residents has increased from 16.9% in 2000 to 30.7% in 2013, and the prevalence of obesity has doubled since the turn of the century. 13 This growing mismatch between unchanging staffing hours and increasing obesity prevalence may lead to greater challenges in properly caring for residents with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Over the past 15 years, staffing at nursing homes has stayed level in terms of nursing aide hours per resident per day. 28 The rate of obesity among nursing home residents has increased from 16.9% in 2000 to 30.7% in 2013, and the prevalence of obesity has doubled since the turn of the century. 13 This growing mismatch between unchanging staffing hours and increasing obesity prevalence may lead to greater challenges in properly caring for residents with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Other literature, including the Long-Term Focus dataset uses this methodology to standardize characteristics over time. 26–28 …”
Section: Methodsmentioning
confidence: 99%
“…With the shift in nursing homes to delivering more postacute care, their capacity for treating and managing complex conditions has increased. 23 Moreover, given the high prevalence of dementia in nursing homes, providers at those facilities may be more used to treating patients with dementia than community-based physicians are.…”
Section: Discussionmentioning
confidence: 99%
“…This file included all existing and closed nursing homes in the United States through 2008; we updated this file using our geo-coded CBS file and with the addition of data on all nursing homes that had opened or closed in 2009 and 2010, as identified in the Online Survey Certification and Reporting (OSCAR) data available for nearly all U.S. nursing homes, both freestanding and hospital based. We chose to include both types of nursing home closures and additions because recent research has shown that freestanding and hospital-based facilities are providing more similar care than in the past; patient acuity and therapy provision have increased in free-standing facilities, while these services have decreased in hospital-based facilities (Tyler et al, 2013). Finally, we used ArcGIS to create 5-mile radii around each U.S. nursing home that had closed between 2006 and 2010.…”
Section: Introductionmentioning
confidence: 99%